Applied calculus of variations for engineers - Komzsik, Louis (Boca Raton, FL : CRC Press, 2014)
The purpose of the calculus of variations is to find optimal solutions to engineering problems whose optimum may be a certain quantity, shape, or function. Applied Calculus of Variations for Engineers addresses this important mathematical area applicable to many engineering disciplines. Its unique, application-oriented approach sets it apart from the theoretical treatises of most texts, as it is aimed at enhancing the engineer's understanding of the topic.This Second Edition text: Contains new chapters discussing analytic solutions of variational problems and Lagrange-Hamilton equations of motion in depth; Provides new sections detailing the boundary integral and finite element methods and their calculation techniques; Includes enlightening new examples, such as the compression of a beam, the optimal cross section of beam under bending force, the solution of Laplace's equation, and Poisson's equation with various methods.
Includes bibliographical references (p. 207-208) and index.
Keywords: Calculus of variations; Engineering mathematics